2019
DOI: 10.1515/biol-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Huaiqihuang Granules adjuvant therapy in children with primary nephrotic syndrome

Abstract: ObjectiveThis study aims to observe the curative effect of Huaiqihuang Granules adjuvant therapy on primary nephrotic syndrome (PNS).MethodsA total of 112 children with PNS were randomly divided into three groups, and changes in serum inflammatory cytokines, interleukin, lymphocyte subsets and immunoglobulin were observed.ResultsBefore treatment, IL-18, TNF-α, CD8+ increased, while IL-10, CD4+, NK cells, IgA, IgG and Foxp3+Treg cells decreased. After Huaiqihuang Granules treatment, IL-18, TNF-α, CD8+ decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Patients with HSPN present high levels of IL-8, CCL2, TNF- α , IL-10, and IL-6 [ 23 , 24 ]. HQH administration elevates Treg and lowers Th17 levels [ 5 , 25 ]. Consistent with previous results, our study showed that Huaier acts on IL6, CCL2, IL-10, and TNF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with HSPN present high levels of IL-8, CCL2, TNF- α , IL-10, and IL-6 [ 23 , 24 ]. HQH administration elevates Treg and lowers Th17 levels [ 5 , 25 ]. Consistent with previous results, our study showed that Huaier acts on IL6, CCL2, IL-10, and TNF.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, glucocorticoid steroids combined with immunosuppressive therapy are recommended to treat HSPN [ 4 ]. However, clinical data suggest that this treatment has evident side effects such as gastrointestinal diseases, oncogenesis, and myelosuppression [ 5 ]. Therefore, it is necessary to identify new, effective, and safe strategies for the treatment of HSPN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation